1991
DOI: 10.1111/j.1365-2729.1991.tb00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Why is science difficult to learn? Things are seldom what they seem

Abstract: The difficulties of learning science are related to the nature of science itself and to the methods by which science is customarily taught without regard to what is known about children's learning. An information processing model is proposed to guide thinking and research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
775
0
93

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 954 publications
(924 citation statements)
references
References 3 publications
15
775
0
93
Order By: Relevance
“…The textbook set analysis revealed that the overall proportion of direct and combined descriptors of SMR add-ons is significantly low through all the curriculum topics (range from 0.00% to 3.31%). That can be connected with the Johnstone's claim 10 that the experienced chemists do the transition between levels of representations very easily and they assumed that learners can do this as easily as they do. These simplified assumptions about learners' easy comprehension and efficient learning with SMRs are reflecting in the low frequency of SMR descriptors, where the informational value of a particular SMR enables the learner a direct recognition of particles, in textbook sets.…”
Section: Holistic Descriptors Of Smr Add-ons Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…The textbook set analysis revealed that the overall proportion of direct and combined descriptors of SMR add-ons is significantly low through all the curriculum topics (range from 0.00% to 3.31%). That can be connected with the Johnstone's claim 10 that the experienced chemists do the transition between levels of representations very easily and they assumed that learners can do this as easily as they do. These simplified assumptions about learners' easy comprehension and efficient learning with SMRs are reflecting in the low frequency of SMR descriptors, where the informational value of a particular SMR enables the learner a direct recognition of particles, in textbook sets.…”
Section: Holistic Descriptors Of Smr Add-ons Usedmentioning
confidence: 99%
“…Namely, based on their own acceptance of the simultaneous use of SMRs as a part of a triple representation of chemistry concepts (submicroscopic, macroscopic and symbolic levels), chemistry educators, such as authors of textbooks, can assume that students can also easily comprehend and efficiently learn with the use of SMRs. 10 However, the understanding of the kinds of information and inferences that the visualisations in various learning materials provide requires explicit instruction and practice. 19 The research indicates that students' successful learning with SMRs is significantly impacted by their representational competence in chemistry.…”
Section: The Context and The Purpose Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This led to my little paper in School Science Review (Johnstone, 1982) and further thought resulted in my later publications (Johnstone, 1991(Johnstone, , 1993(Johnstone, , 2000 cited in the introduction of this present book. The triangle which I proposed had its origins in geology where mineral compositions were set out as combinations of silicon dioxide, magnesium oxide and calcium oxide.…”
Section: Forewordmentioning
confidence: 99%
“…De acordo com Johnstone (1991), os modos representacionais macroscópicos, submicroscópicos e simbólicos compõem o ensino de química. As representações mentais adquiridas a partir de percepções dos sentidos formam o modo macroscópico.…”
Section: Visualizações E Os Modos De Representação Do Conhecimento Quunclassified